The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1158/0008-5472.can-06-0563
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Fanconi Anemia/BRCA Pathway and Recombination Repair in the Cellular Response to Solar Ultraviolet Light

Abstract: Recombination repair plays an important role in the processing of DNA double-strand breaks (DSB) and DNA cross-links, and has been suggested to be mediated by the activation of the Fanconi anemia (FA)/BRCA pathway. Unlike DNA damage generated by ionizing radiation or DNA crosslinking, UV light-induced DNA damage is not commonly thought to require recombination for processing, as UV light does not directly induce DSBs or DNA cross-links. To elucidate the role of recombination repair in the cellular response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 48 publications
6
33
0
Order By: Relevance
“…As demonstrated previously (Dunn et al, 2006), physiological doses of SSL (containing 100, 200, or 300 J m À2 UVB) induces time-and dose-dependent monoubiquitination of the FANCD2 protein (Figure 1a Fibroblasts from patients with FANCA or FANCC were found not to be hypersensitive to UVB or to UVA (Supplementary Figure S1 online). As these cells are unable to ubiquitinate FANCD2 and to activate the FA/BRCA pathway in response to any stimulus, this indicates that a lack of FA/BRCA pathway activation does not increase acute toxicity of either UVB or UVA.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…As demonstrated previously (Dunn et al, 2006), physiological doses of SSL (containing 100, 200, or 300 J m À2 UVB) induces time-and dose-dependent monoubiquitination of the FANCD2 protein (Figure 1a Fibroblasts from patients with FANCA or FANCC were found not to be hypersensitive to UVB or to UVA (Supplementary Figure S1 online). As these cells are unable to ubiquitinate FANCD2 and to activate the FA/BRCA pathway in response to any stimulus, this indicates that a lack of FA/BRCA pathway activation does not increase acute toxicity of either UVB or UVA.…”
Section: Resultssupporting
confidence: 69%
“…As demonstrated previously (Dunn et al, 2006), a physiological dose of both SSL (containing 200 J m À2 UVB) and IR (10 Gy) induces nuclear foci of g-H2AX, although in a very different time-course and pattern. UVB-induced foci, in contrast to IR-induced ones, are only seen in a subset of cells and only with a delay of 45 minutes.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…For example, it was recently reported that ultraviolet (UV) light, which does not directly introduce DSBs or DNA interstrand cross-links, can activate the FA/BRCA pathway as evidenced by FANCD2 monoubiquitination [20]. In that study, it was suggested that the BRCA-FA pathway may be responsible for recombinational repair of stalled replication forks when nucleotide excision repair or translesion bypass fail.…”
Section: Brca-fa Dna Damage Response Pathwaymentioning
confidence: 99%